Assessment Of Immediate and Short-Term Changes in Left Ventricular Systolic Function After Interventional Patent Ductus Arteriosus (PDA) Closure by Transthoracic Conventional Echocardiography and Tissue Doppler - Aboudeif Othman, Mahmoud; Sharaf, Eman; Ahmed Attia, Wael; Hany Moussa, Mohamed; A. El Desouky, Manar (Journal of Neonatal Surgery, 2025)
Background: Failure of the ductus arteriosus to close naturally within 24 – 48 hours post naturally usually results into significant hemodynamic compromise that necessitates its early closure either interventionally or surgically. Aim: To assess the left ventricular (LV) dimensions and systolic function within the first week and three months after interventional PDA closure. Patients and methods: Infants and children (6month -12years) undergoing transcatheter PDA closure. Pre closure and catheter data were collected and a comprehensive transthoracic echocardiography utilizing two-dimensional (2D) and Tissue doppler Imaging (TDI) has been performed within the first week and 3 months post closure. Results: 30 patients who underwent catheterization closure of PDA consisting of 22 females (73%) and 8 males (27%) were assessed. Although pre-closure 2D assessment did not show any LV systolic dysfunction, our first echo post closure documented 4 (13%) patients with LV systolic dysfunction as well as 3 (10%) patients with right ventricular (RV) systolic dysfunction using two-dimensional imaging. Using TDI 16 (53%) patients had RV diastolic dysfunction of whom 10 (33%) patients had LV diastolic dysfunction where 3 patients had improved LV diastolic function over follow up. Conclusion: Study shows 13.3% of patients develop transient LV systolic dysfunction post-PDA catheter closure (75% resolve by 3month), with 53% having Right RV diastolic dysfunction, necessitating TDI follow-up.